Issues in the statutory housing sale agreements in Peninsular Malaysia: A case study of abandoned housing projects - Md Dahlan, Nuarrual Hilal (2015)
The use of statutory housing sale agreements (‘the said agreements’) as enshrined under the Housing Development (Control & Licensing) Regulations 1989 is mandatory for all housing developers in Peninsular Malaysia. The use of the said agreements is to ensure protection to house purchasers against irresponsible housing developers. However, in practice, it is evident that the terms of the said agreements are inadequate to provide purchasers with the required protection particularly in abandoned housing projects. This paper aims to highlight this issue. This paper is also a fruit of a research exercise using legal research and qualitative case study methodologies. It finds that there are certain lacunae in the terms of the said agreements that have caused the said agreements inability to face the problems of abandoned housing projects to the detriment of the house purchasers’ rights. Further, there are certain housing transaction practices that have caused grievances to the house purchasers. The author provides, at the ending part of this paper, some proposals to overcome the highlighted problems. This is a part of the initiatives to strengthen the said agreements to become more protective to house purchasers.